Mathematical competencies with applications of mirror classes in regular basic education - Maruja Dionisia Baldeón De La Cruz; Melba Rita Vasquez Tomás; Judith Soledad Yangali Vicente; Jhon Holguin-Alvarez (International Journal of Evaluation and Research in Education (IJERE), 2023)
The problem about learning in mathematics lies in the lack of application of teaching strategies for the resolution of the calculation in mathematical problems, problems of movement, mathematical regularity, equivalence, and uncertainty; in populations with difficulties to learn collaboratively. Here the application of mirror classes in populations with interactive problems is demonstrated, thus contributing to strengthening their knowledge from cooperative information management, the use of analysis skills based on co-evaluation. In this sense, the purpose of the study was to evaluate the mirror class, as a pedagogical strategy, in order to optimize the competence of solution of quantity problems in basic school students of two educational institutions in Lima, Peru. The study was conducted under the action research approach where the diagnostic and exit test, question guide and field diary were the instruments used for data collection. It was concluded that the mirror class as a pedagogical strategy favors the optimization of competition and solves quantity problems in basic education students. So, they also developed concrete knowledge, to assign them in cognition more enduringly as a form of social learning.